Introductory Note to the Document "Il sistema di collegamenti bibliografici nell'archivio della cooperazione di T. Giordano, con la collaborazione di S. Peruginelli" - Giovanni Bergamin (JLIS.it, 2020)
The purpose of this article is to introduce a seminal 1984 document on the structure of the “system of bibliographic links” of the Italian national library service (named SBN or Servizio Bibliotecario Nazionale). To some extent thirteen years before FRBR, the Entity-Relationship Model has been used to identify Entities, Attributes and Relationships within bibliographic records. The 1984 document can also be seen as a first step of a long path (which has not yet been concluded) of use of E-R model: also the IFLA LRM (2017) claims that it has been developed within the framework of an E-R model.